USING EXPRSSION CARD MEDIA TO IMPROVE THE STUDENTS’SPEAKING SKILL AT THE SECOND GREAT OF SMA NEGERI 1 PAREPARE - Widya Pribadiyanti Areski; Muzdalifah Muhammadun; Amzah Selle (Inspiring: English Education Journal, 2019)
This research aims to see the students’ speaking skill before and after learning process by using expression card media at the second grade of SMA Negeri 1 Parepare. The results of the research are useful for the teacher and students. The teacher should aware that it is important to supplied the technique or strategy before teaching and the students also can be easier to express their ideas, make the students more active in learning process. The subject of this research is XI IIS4 class which is consisted of 30 students. The sample was taken by using simple random sampling. The design in this research was pre-experimental with pre-test and post-test design. The student did the pre-test, got the treatment and did the post-test. Then the criteria of speaking skills are fluency, accuracy, content, pronunciation and they were usedto measure the students’ speaking skill. It aimed to know whether using expression card media can improve the students’ speaking skill. The result in this research was indicated that there was improvement of the students’ speaking skill. It was indicated by the students’ mean score of post-test (73.3) was greater than pre-test (41.9). Even, for the level significant (p) 5% and (df) = N-1=30-1=29, and the value of table is 1.699, while the value of t-test is 16.18. it means that, the t-test value is greater than t-table (16.18 ≥ 1.699). Thus, it can be concluded that the students’ speaking skill is significant better after getting the treatment. So, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is fail rejected.